2019
DOI: 10.3390/ijerph16173127
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Exposure to Ambient Air Pollution: A Systematic Review in the WHO European Region

Abstract: Ambient air pollution is a long-standing and significant public health issue. The aim of this review is to systematically examine the peer-reviewed evidence on social inequalities and ambient air pollution in the World Health Organization European Region. Articles published between 2010 and 2017 were analyzed in the review. In total 31 articles were included in the review. There is good evidence from ecological studies that higher deprivation indices and low economic position are usually linked with higher lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(67 citation statements)
references
References 63 publications
3
56
0
1
Order By: Relevance
“…Ethnicity/race has interaction with many social, psychosocial and environmental factors. In the US and Europe, minority neighborhood tends to be exposed to heavier air pollution, indicating that ethnic/racial difference may result from residential segregation 15,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Ethnicity/race has interaction with many social, psychosocial and environmental factors. In the US and Europe, minority neighborhood tends to be exposed to heavier air pollution, indicating that ethnic/racial difference may result from residential segregation 15,17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is expected to increase wildfire risk, which, in turn, will increase particulate matter levels, and associated health risks [23]. Exposure to PM is not uniform among population groups; higher levels of PM have been found to be associated with higher deprivation indices and low economic position in a recent review [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the neighborhood SES indicator in this study did not re ect participants with lower socio-economic status. In literature, the pattern of air pollution is often described as U-shaped , although the most deprived areas have the highest levels of poor air quality, the least deprived areas also experience higher levels of air pollutants than some other social groups [37]. In our cohort, the mean ADI was 18.1% for lower educated mothers, 15.3% for medium education mothers and, as described in literature, we observed a slightly higher ADI of 15.6% for higher educated women.…”
Section: Discussionmentioning
confidence: 99%
“…neighborhood SES and residential exposure to noise. A systematic review in the World Health Organization (WHO) European Region showed that lower neighborhood SES is usually linked with higher levels of air pollutants [37]. Independent from higher levels of exposure, deprived mothers may have a higher vulnerability, leading to more pronounced adverse health effects of a given environmental exposure [38].…”
Section: Potential Covariates Of Hair Cortisol Concentrationsmentioning
confidence: 99%